2017
DOI: 10.1186/s40104-016-0140-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liquid feeding of corn condensed distiller’s solubles and whole stillage on growth performance, carcass characteristics, and sensory traits of pigs

Abstract: BackgroundThe immense growth in global bioethanol production has greatly increased the supply of by-products such as whole stillage and condensed distiller’s solubles, which could be potentially used for animal feeding. The objective of this study was to investigate effects of liquid feeding high levels of corn condensed distiller’s solubles (CCDS) and whole stillage (CWS) on growth performance, carcass characteristics, belly firmness and meat sensory traits of pigs.MethodsA total of 256 pigs were blocked by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
2
0
5
Order By: Relevance
“…Several studies have investigated the effects of providing BSF larvae to both broilers and laying hens. In broilers, BSF larvae meal is a good source of apparent metabolizable energy and digestible amino acids ( De Marco et al, 2015 ; Schiavone et al, 2017b ) and has been shown to improve growth rate ( Oluokun, 2000 ). Feed containing BSF larvae oil has been shown to improve broiler chicken feed conversion ratio compared to corn oil and coconut oil ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effects of providing BSF larvae to both broilers and laying hens. In broilers, BSF larvae meal is a good source of apparent metabolizable energy and digestible amino acids ( De Marco et al, 2015 ; Schiavone et al, 2017b ) and has been shown to improve growth rate ( Oluokun, 2000 ). Feed containing BSF larvae oil has been shown to improve broiler chicken feed conversion ratio compared to corn oil and coconut oil ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…En conjunto, estos resultados indican que la alimentación húmeda de cerdos expuestos a condiciones de temperatura ambiente elevada podría mejorar no solamente el consumo de alimento sino también la eficiencia en la utilización del alimento. Yang et al (6) reportaron una menor GDP y EA en cerdos en crecimiento-finalización alimentados con una dieta líquida con subproductos de la industria del etanol, en comparación con los cerdos alimentados con una dieta húmeda a base de maíz y harina soya. Esto sugiere que, además del tipo de alimentación (húmeda o seca), los ingredientes utilizados también son importantes en la eficiencia productiva.…”
Section: Discussionunclassified
“…Alimentación húmeda ha demostrado reducir el estrés en la transición de dieta líquida a sólida de lechones destetados (1,2,3) y esto puede tener efectos beneficiosos tales como la reducción del uso de antibióticos en los sistemas de producción actuales (4,5) . Además, la alimentación húmeda, mejora el consumo de agua y alimento (3,6) , y el suministro de nutrientes en cerdos crecimiento-finalización (7) , comparada con la alimentación seca, pudiendo esto favorecer el comportamiento productivo (4) sin afectar el contenido de grasa y calidad de la canal en cerdos (1,5) .…”
Section: Introductionunclassified
“…Це може мати позитивні наслідки, такі як зменшення використання антибіотиків у поточних системах виробництва (Moon et al, 2004;Zoric et al, 2015). Крім того, вологий корм покращує споживання води та корму (Moon et al, 2004;Yang et al, 2017) і збільшує постачання поживних речовин поросятам-сосунам (NRC, 2012) порівняно з сухим кормом, що, можливо, сприяє вищій продуктивності (Zijlstra et al, 1996;Brooks et al, 2001;Zoric et al, 2015). Інші автори (Chae, 2000) додають, що збільшення швидкості росту поросят значною мірою пов'язане зі збільшенням добровільного споживання корму та зменшенням втрат корму, що підвищує ефективність годівлі (Byrgesen et al, 2021;Boston et al, 2022;Chem et al, 2023).…”
Section: вступunclassified